The Influence of Human Resource Practices on Employee Retention - Kochachathu, Purushothaman (2010)
Employee retention is an important issue that companies should focus on. Companies should identify the factors determining employee retention and strategically move towards improving and implementing necessary policy in those areas efficiently to retain their employees. In current situation Companies are losing their key employees and not sensitive on why their key talent is leaving. The objective of this study is to identify the influence of human resource practice on employee retention in Intel Malaysia. A survey was sent to 368 employees and 130 of them responded. The result was analyzed using the SPSS Version 12, the regression analysis found that there is a significant relationship between 2 independent variables. The variables identified for the study are work environment and job design, hires and promotions, employee recognition rewards and compensation and finally employee performance assessment and development. Among the Independent variables it was found that employee recognition rewards and compensation followed by Work environment and job design are the influencing factor for employee retention in Intel Malaysia.